BENEFICIAL LITERARY WORKS IN TEACHING ENGLISH - Atadjanova, D.A.; Omarova, N.M. (SCIENCE and SOCIETY, 2024)
This article is about literary works that are beneficial to learn English language successfully. It provides readers with the information about the books that can be used in teaching process.